2008
DOI: 10.2174/1874276900802010030
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Significantly Contribute to Vasculatures in Human and Mouse Breast Tumors

Abstract: Abstract:The development of blood supply is crucial to the growth and progression of breast tumors. However, the contribution and role of endothelial progenitor cells (EPCs) in blood vessel formation in human breast tumors is undefined. Here, we demonstrate for the first time that ~68% of the cells integrated into vasculatures in late stage human breast tumors express CD34 and CD133 (the putative EPC markers). We also demonstrate that metastatic human breast cancer and mouse mammary gland carcinomas (MGCas) ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…G-CSF is produced in advanced human and murine breast cancers (39). Breast tumor derived CSF-1 increased hematopoietic stem cells and endothelial progenitor cell numbers in the mouse (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-CSF is produced in advanced human and murine breast cancers (39). Breast tumor derived CSF-1 increased hematopoietic stem cells and endothelial progenitor cell numbers in the mouse (39).…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is produced in advanced human and murine breast cancers (39). Breast tumor derived CSF-1 increased hematopoietic stem cells and endothelial progenitor cell numbers in the mouse (39). In prior studies investigating the potential role of macrophages in mammary tumor progression, the polyoma middle T antigen was expressed in the murine mammary gland and the animals crossed with mice expressing a mutation of the CSF-1 receptor (34).…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies were directed to von Willebrad (vWF) (DAKO, Carpinteria, CA), c-Kit, CD133, and CD31 (BIOCARE Medical, Concord, CA) (24). Heat-induced epitope retrieval was performed on formalin-fixed and paraffin-embedded sections by incubating the sections in citrate buffer with 5% Tween 20 (pH 6.0) at 100°C for 20 minutes and allowed to cool for 20 minutes prior to staining.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies had suggested an increased abundance of VEGF in the circulation of MMTV-ErbB2 transgenic mice (180 mg/ml versus 43 mg/ml). 41 To determine the NF-B-regulated proteins secreted by NAFA cells, the supernatant of the NAFA and NAFA-I B␣SR were analyzed for secreted chemokines and cytokines using cytokine arrays ( Figure 7A). 34 Subtractive analysis was then conducted to identify NF-B-regulated secreted proteins ( Figure 7B).…”
Section: Nf-b Regulates Tumor Angiogenesis Via Vegf In Mammary Epithementioning
confidence: 99%